A Numerical Simulation of Machining 6061 Syntactic Foams Reinforced with Hollow Al2O3 Shells - Kevin Thomas; Sathish Kannan; Mohammad Nazzal; Salman Pervaiz; Ramanujam Karthikeyan (Metals, 2022)
Aluminum closed cell syntactic foams possess reduced density, higher peak compression strength, and lower coefficient of thermal expansion and thermal conductivity compared to metal alloys. However, the industrial mass production of these complex material systems presents a significant problem in the form of poor machinability. In order to address this concern and to increase the use of this potential cost- and energy-saving system, a two-dimensional numerical model using the AdvantEdgeTM machining software was developed. For the verification of the numerical model, machining trials in dry conditions were conducted on different samples using a SandvikTM carbide-coated insert having a 6° rake angle and a 7° clearance angle. The hollow alumina shell diameter and volume fraction were found to profoundly affect the magnitude of the generated machining forces. This study showed an increase in machining force by almost 25% for syntactic foams reinforced with hollow alumina shells of higher volume fraction and coarser diameters. The cutting conditions to obtain a favorable stress diastribution in the syntactic foam’s machined sub-surface were identified.